Comparison of the Effect of Two Hybrid Models of Problem-Based Learning Implementation on the Development of Transversal and Research Skills and the Learning Experience - Carrió, Mar; Baños, Josep-E; Rodríguez, Gemma (Frontiers in Education, 2022)
Problem-based learning (PBL) provides an encouraging learning environment to develop transversal and research thinking skills. However, how PBL is implemented into a curriculum can be critical for achieving these outcomes. This study compares two hybrid PBL implementation models applied in a health sciences school: a PBL-module integrated into the subjects of a traditional curriculum and full interdisciplinary PBL-courses. 651 students were involved, with 330 taking the PBL-module and 277 taking the PBL-courses. Students’ and tutors’ perceptions about the acquisition of the skills as well as their satisfaction with the learning experience were compared. The results showed that in the interdisciplinary PBL-courses, both students and tutors perceived a significantly higher acquisition of these skills. In addition, they also find the methodology more useful and are more satisfied with the learning experience than in the PBL-modules. A strong correlation was also observed between the acquisition of transversal and research skills and the perceived usefulness of PBL and overall satisfaction with the experience. This study provides new evidence on the characteristics of PBL that favor the development of these skills.